Social Responsibility in Global Supply Chain: Research Trend from 1999 to 2014 - Md Tareq Bin Hossain; Roslan Abdul Hakim; Che Azlan Bin Taib; Md Julker Naim (International Journal of Supply Chain Management, 2017)
The well know term of corporate social responsibility (CSR) or simply social responsibility for business organization refers to the concept where the companies integrate social and environmental concerns into their day to day business operations. The aim of this article is to observe the social responsibility research trend within global supply chain. Based on the review of prior literature, it is easy to say that the concept of CSR has received overwhelming attention by the professional and academia of all over the global. Even though, there is debate whether the companies have any responsibility for their supplier premises, more literatures are confirming that the business organizations are considering carefully the issues of CSR within supply chain. Since the concept of CSR covering enter arena of business, it is interesting to work on literature and discover the recent research trend on CSR study within supply chain. Current study has taken an initiative to determine the drivers that influence CSR practice within the supply chain based on literature review for sixteen years Finding suggests, there are drivers influences CSR practice within supply chain.